Return to sport following lateral ankle ligament repair is under-reported: a systematic review. Issue 5 (8th July 2017) - Hunt, Kenneth J; Fuld, Richard S; Sutphin, Brittan S; Pereira, Helder; D'Hooghe, Pieter
Abstract : Importance: Ankle sprains are the most commonly occurring musculoskeletal injury. Reconstruction of the lateral ligament complex is often required for athletes with recurrent instability, or high-grade acute sprains, in order to return to their pre-injury level of sport. Objective: The purpose of this systematic review was to evaluate the spectrum, prevalence and quality of evidence regarding return to sport timeline following lateral ligament surgery. Evidence review: A search was conducted of Embase and Medline databases from the earliest possible entry to November 2016. Studies reporting a timeline regarding return to play (RTP) following lateral ankle ligament reconstruction were included in this review. Findings: Of 3184 total articles, 20 articles evaluating 489 athletes met the criteria and were included for review. Thirteen of the 20 papers were used to calculate a weighted mean time to RTP of 4.7 months. Overall, both the frequency and quality of RTP criteria and reporting were very low. Conclusions and relevance: The current review identifies a clear deficiency in the literature pertaining to consistent, meaningful postoperative RTP timeline following lateral ankle ligament repair. Published studies vary considerably in the metrics used for measuring patient-reported outcomes, and very few actually track them. Further studies on outcomes following ankle ligament repair should include clear and consistent metrics for return to sport and level of play. Standardised and reproducible criteria for reporting RTP for athletes will improve the utility and applicability of outcomes data as surgical and rehabilitative techniques continue to advance. Level of evidence: Systematic review of level I–IV studies, level IV.